1994
DOI: 10.1161/01.atv.14.3.325
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exercise training on the chemical composition of plasma LDL.

Abstract: The purpose of the present study was to determine the effects of exercise training on the chemical composition of plasma low-density lipoprotein (LDL). Thirteen men (mean age±SE, 47.2±1.5 years) were examined before and after 14 weeks of endurance-oriented exercise training (3 to 4 d/wk, 30 to 45 min/d). Although calculated plasma LDL concentrations remained unaltered (3.49±0.24 versus 3.65±0.23 mmol/L), changes in the chemical composition of LDL (increased LDL free cholesterol, cholesterol ester, and phospnol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
2

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 50 publications
1
16
0
2
Order By: Relevance
“…In studies that have reported an increase in HDL cholesterol 38 and a decrease in LDL cholesterol 39 and triglycerides, 40,41 subjects have usually trained at between 70% to 90% of their predetermined maximum heart rate, 3 to 5 times per week for at least 14 weeks. [41][42][43] Furthermore, Superko reported jogging for at least 6 km/wk for 7 months was required to induce a change in lipid profile.…”
Section: Discussionmentioning
confidence: 99%
“…In studies that have reported an increase in HDL cholesterol 38 and a decrease in LDL cholesterol 39 and triglycerides, 40,41 subjects have usually trained at between 70% to 90% of their predetermined maximum heart rate, 3 to 5 times per week for at least 14 weeks. [41][42][43] Furthermore, Superko reported jogging for at least 6 km/wk for 7 months was required to induce a change in lipid profile.…”
Section: Discussionmentioning
confidence: 99%
“…For example, exercise-induced fat loss was significantly associated with increases in HDL cholesterol 55 , changes in the LDL cholesterol to HDL cholesterol ratio 56 , fasting TAG concentrations 56,57 and with changes in the chemical composition of LDL (more cholesterol-enriched and protein-poor) 57 . Changes in the amount and distribution of body fat with exercise thus probably contribute towards the effects on lipoprotein metabolism attributable to exercise.…”
Section: Health Benefit From Enhanced Metabolic Capacity For Tag-richmentioning
confidence: 99%
“…48 The role of smoking in oxLDL has been documented previously. [20][21][22][23] Few studies indicated an effect of physical activity on the chemical composition of LDL, 49,50 and it is unknown whether physical activity influences oxLDL-Ab or oxLDL-ICs. Therefore, screening children and young adults for abnormal levels of oxLDLICs may set the stage for prevention trials using vitamin E supplementation.…”
Section: Commentmentioning
confidence: 99%